Chemical composition and synergistic effect of three Moroccan lavender EOs with ciprofloxacin against foodborne bacteria: a promising approach to modulate antimicrobial resistance. (27th February 2021) - Nafis, A.; Ouedrhiri, W.; Iriti, M.; Mezrioui, N.; Marraiki, N.; Elgorban, A.M.; Syed, A.; Hassani, L.
Abstract: The aim of this study was to determine the chemical profile of the essential oils (EOs) of three Moroccan lavender species ( Lavandula pedunculata, LP; Lavandula angustifolia, LA; and Lavandula maroccana, LM) and to investigate, for the first time, the synergistic effect of the optimal mixture of the EOs with conventional antibiotic ciprofloxacin against three pathogenic foodborne bacteria. Gas chromatography/mass spectrometry analysis showed that eucalyptol (39·05%), camphor (24·21%) and borneol (8·29%) were the dominant compounds of LA‐EO. LP‐EO was characterized by the abundance of camphor (74·51%) and fenchone (27·06%), whereas carvacrol (42·08%), camphor (17·95%) and fenchone (12·05%) were the main constituents of LM‐EO. EOs alone or combined showed a remarkable antimicrobial activity against the tested bacteria with minimum inhibitory concentrations (MICs) ranging from 3·53 to 15·96 mg ml −1 . The optimal mixture, calculated using a mixture design, corresponded to 19% LA, 38% LP and 43% LM. All combination of the EOs and the best EO mixture with ciprofloxacin exhibited a total synergism with fractional inhibitory concentration index values ranging from 0·27 to 0·37. The best EO mixture showed the highest gain of 128‐fold, especially against Salmonella spp., more than that found testing the EOs separately. These findings should be taken into consideration for a possible application in the pharmaceutical and food industries. Abstract : Significance and impact of the study: The combination of essential oils (EOs) with conventional antibiotics is a novel and promising strategy to increase and restore their antimicrobial potential. We demonstrated, for the first time, that the combination of a mixture of Moroccan lavender EOs with ciprofloxacin gives 128‐fold as gain of antibiotic MIC which is more than that found when EOs were used separately.